Spontaneous Chloroplast Mutants Mostly Occur by Replication Slippage and Show a Biased Pattern in the Plastome of Oenothera . Issue 4 (6th April 2016) - Massouh, Amid; Schubert, Julia; Yaneva-Roder, Liliya; Ulbricht-Jones, Elena S.; Zupok, Arkadiusz; Johnson, Marc T.J.; Wright, Stephen I.; Pellizzer, Tommaso; Sobanski, Johanna; Bock, Ralph; Greiner, Stephan
Abstract : Spontaneous chloroplast mutants mostly occur by replication slippage and display a mutation spectrum very different from that in the eukaryotic nucleus and that of bacteria. Abstract: Spontaneous plastome mutants have been used as a research tool since the beginning of genetics. However, technical restrictions have severely limited their contributions to research in physiology and molecular biology. Here, we used full plastome sequencing to systematically characterize a collection of 51 spontaneous chloroplast mutants in Oenothera (evening primrose). Most mutants carry only a single mutation. Unexpectedly, the vast majority of mutations do not represent single nucleotide polymorphisms but are insertions/deletions originating from DNA replication slippage events. Only very few mutations appear to be caused by imprecise double-strand break repair, nucleotide misincorporation during replication, or incorrect nucleotide excision repair following oxidative damage. U-turn inversions were not detected. Replication slippage is induced at repetitive sequences that can be very small and tend to have high A/T content. Interestingly, the mutations are not distributed randomly in the genome. The underrepresentation of mutations caused by faulty double-strand break repair might explain the high structural conservation of seed plant plastomes throughout evolution. In addition to providing a fully characterized mutant collection for future research on plastid genetics, gene expression, and photosynthesis, our work identified the spectrum of spontaneous mutations in plastids and reveals that this spectrum is very different from that in the nucleus.